IMPORTANCE OF INFORMATION TECHNOLOGY TODAY - Isomiddinov Bekzodjon Ozodjon o’g’li (Journal Park Publishing, 2024)
In modern life, information technology penetrates into all spheres of our lives. As a result, high-quality IT services have become very important today. One of such areas is telemedicine. Telemedicine allows for providing remote medical assistance and monitoring patients' health through online consultations. The development of this field requires the application of modern high-tech solutions. In this regard, the created consortium develops the main technological standards and contributes to the development of the medical industry. Innovative products and solutions are created with the support of the state to maintain health and ensure order in this area.
Keywords: Healthcare, medicine, IT, medical consultations, telemedicine.